MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANIMASI PADA MATERI STATISTIKA UNTUK SISWA KELAS 7 SMP - Widjayanti, Wigita Rezky; Masfingatin, Titin; Setyansah, Reza Kusuma (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
This study aims to determine the feasibility of interactive learning media based on animation in learning of mathematics. This research and development consists of the initial investigation, design, construction, test, evaluation and revision, and implementation phase. This study only focused until the test, evaluation and revision phase. The results: 1) the animation-based interactive learning media expressed a very valid views of the results the average valuation of 89.05% media validator; 2) interactive learning media based on animation stated the practical results of the the average obtained from the student response sheet now reaching 87.95% gave a positive response; 3) interactive learning media based on animation effective which obtained from the percentage of the students who complete that is equal to 87.50%. Based on the results of the study, it can be concluded that interactive learning media based on animation appropriate to be used in mathematics learning in statistical material for 7th grade. DOI: 10.22342/jpm.13.1.6294.101-112